Association between Optical Coherence Tomography and Fluorescein Angiography based retinal features in the diagnosis of Macular Edema. (January 2020) - Ajaz, Aqsa; Aliahmad, Behzad; Kumar, Himeesh; Sarossy, Marc; Kumar, Dinesh K.
Abstract: The association between optical coherence tomography (OCT) and the geometrical vascular parameters obtained from the fluorescein angiography (FA) of the eyes with macular edema (ME) was investigated. Data from 82 untreated eyes with ME were studied. Fractal dimension (FD), simple tortuosity, branching angle, total angle count and vessel to background ratio were the five vasculature parameters from FA that were studied. The four OCT features measured were central retinal/foveal thickness, average para-fovea thickness, average peri-fovea thickness and OCT volume. The four OCT parameters showed a significant difference between ME requiring treatment (MERT) and non-MERT eyes with the central retinal thickness (threshold at 300 μm) and average para-fovea thickness (threshold at 338.5 μm) as most significant. The results also indicate that FD from the FA of retinal vessels in the macular region was associated with the changes in retinal thickness and that OCT parameters can potentially be used for directly identifying ME. Graphical abstract: Image 1 Highlights: Investigated the association between OCT and FA vessel features in diagnosis of Macular Edema. Five retinal features from FA and four OCT features were studied for this analysis. The results revealed that OCT parameters as significant features for classifying Macular Edema requiring treatment (MERT). Retinal thickness on the OCT corresponds with a substantial degree of correlation with retinal vasculature changes on FA. Fractal Dimension (FD) was identified as the most sensitive features to changes in retinal thickness associated with ME.